Pengaruh Kepemilikan Institusional, Kepemilikan Manajerial, dan Pengungkapan Corporate Social Responsibility terhadap Nilai Perusahaan Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia - Kadek Ria Citra Dewi; I Gede Sanica (Universitas Pendidikan Nasional, 2017)
The main goal of company is to improve the value of the company. The company's value can increase wealth for shareholders. Factors that may affect the value of the company are the ownership structure of the company and corporate social responsibility. This study aims to determine the effect of institutional ownership, managerial ownership, and corporate social responsibility disclosure to firm value. Firm value in this study as proxy for the value of Tobin’s Q. The population of this research is manufacturing companies listed in Indonesia Stock Exchange (IDX) in the period 2013-2015. The method of analysis in this study using multiple linier regression. The results of this study show that institutional ownership and managerial ownership does not affect the value of the firm, while the corporate social responsibility disclosure has positive affect on firm value. Keywords: firm value, institutional ownership, managerial ownership, corporate social responsibility